Entrepreneurial interest and academic performance in Nigeria: evidence from undergraduate students in the University of Ibadan (2017)
Entrepreneurial interest among the youth population is a panacea for unemployment especially due to high turnout of educated individuals in the labour force. This paper provides findings on the factors that determine entrepreneurship interest among the youth population in Nigeria using the University of Ibadan as a case study. Empirical results on whether engagement in entrepreneurial activities interferes with academic performance; extent of involvement and gender differences are also presented. The logit and multinomial logit models were used to examine the factors that influence entrepreneurship interest and interference with academic performance, respectively. Descriptive statistics and the T test were employed in examining the extent of involvement and whether there is a statistically significant difference across gender. The results showed that subjective norm, perceived behavioural control and family business background significantly predicts students’ interest in entrepreneurship. Engagement in entrepreneurial activity has no significant effect on students’ academic performance. Findings suggest relatively low entrepreneurial engagement among students with significant differences across gender.